Spermatogenesis and the Evolution of Mammalian Sex Chromosomes. Issue 9 (September 2018) - Larson, Erica L.; Kopania, Emily E.K.; Good, Jeffrey M.
Abstract : Developmental constraint and sexual conflict shape the evolution of heteromorphic sex chromosomes. These contrasting forces are perhaps strongest during spermatogenesis in species with XY males. In this review, we consider how the unique regulatory environment and selective pressures of spermatogenesis interact to impact sex chromosome evolution in mammals. We explore how each developmental phase of spermatogenesis influences sex chromosome gene content, structure, and rate of molecular evolution, and how these attributes may contribute to speciation. We argue that a developmental context is fundamental to understanding sex chromosome evolution and that an evolutionary perspective can shed new light on our understanding of sperm development. Highlights: Selective pressures exerted by the regulatory environment during spermatogenesis, together with sexual selection and genomic conflict, shape the unique evolutionary dynamics of the mammalian sex chromosomes. The X chromosome is enriched for male-biased genes expressed during the proliferative mitotic phase of spermatogenesis, and these genes tend to evolve faster than autosomal genes. The regulatory constraints of meiotic sex chromosome inactivation (MSCI) shape the evolution of sex chromosome gene content by selecting against sex-linked meiotic genes. Postmeiotic sex chromosome repression (PSCR) has driven the expansion of sex-linked ampliconic genes, possibly through dosage-dependent genomic conflict between the X and Y chromosomes. Each of these stages shapes the divergence of the sex chromosomes and could contribute to the evolution of reproductive barriers between species. Disruption in the epigenetic silencing of the sex chromosomes may be a general mechanism underlying the evolution of hybrid male sterility.